Biomarker‑driven phase Ib clinical trial of OPB‑111077 in acute myeloid leukemia. (2022) - Martínez‑López, Joaquín; Montesinos, Pau; López‑Muñoz, Nieves; Ayala, Rosa; Martínez‑Sánchez, Pilar; Gorrochategui, Julian
No abstract available